The supervirulence plasmid pToK47 from Agrobacterium tumefaciens A281 Improves Transformation efficiency of Hevea brasiliensis - Pappusamy, Arokiaraj; R, Leelawathy; Hoong, Yeet Yeang (Science Publications, 2009)
Problem statement: The present study investigates the ability of the pTok47 supervirulence plasmid form Agrobacterium tumefaciens A281 to enhance genetic transformation in Hevea brasiliensis.